The polynomial p(x) is given: p(x)=x^3+2x^2-5x-6, express p(x) as the product of three linear factors

p(x)=x3+2x2-5x-6

      =x(x2+2x-5)-6

      =x(x2+2x+1-6)-6 as we know (x+1)2=x2+2x+1,5 can be expressed 1-6

      =x[(x+1)2-6]-6

      =x(x+1)2-6x-6

      =x(x+1)2-6(x+1)

      =(x+1)[x(x+1)-6]

      =(x+1)(x2+x-6) here, -6 can be expressed as -2*3, and -2+3=1 

      =(x+1)(x+3)(x-2)

 

Answered by Jingyi B. Maths tutor

12993 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate the following: 5x^3


How do you find a turning point of a function using differentiation?


Show that the line y = x - 7 does not meet the circle (x + 2)^2 + y^2 = 33.


The point on the circle x^2+y^2+6x+8y = 75 which is closest to the origin, is at what distance from the origin? (Taken from an MAT paper)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences